2017
DOI: 10.1167/iovs.17-22697
|View full text |Cite
|
Sign up to set email alerts
|

Can Probability Maps of Swept-Source Optical Coherence Tomography Predict Visual Field Changes in Preperimetric Glaucoma?

Abstract: Structural changes on SS-OCT probability maps could detect or predict VF changes using SAP, in a considerable number of PPG eyes. Careful comparison of probability maps with SAP results could be useful in diagnosing and monitoring PPG patients in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…Hood et al 31 reported that a single wide scan in SS-OCT contains the information needed to diagnose early glaucoma with excellent sensitivity and specificity. In another study, 32 structural changes shown on SS-OCT can detect or estimate VF damage even in preperimetric glaucoma.…”
Section: Discussionmentioning
confidence: 96%
“…Hood et al 31 reported that a single wide scan in SS-OCT contains the information needed to diagnose early glaucoma with excellent sensitivity and specificity. In another study, 32 structural changes shown on SS-OCT can detect or estimate VF damage even in preperimetric glaucoma.…”
Section: Discussionmentioning
confidence: 96%
“…Shin et al 7 found that wide-field SS-OCT images were significantly more accurate than SD-OCT images at predicting a 24-2 VF. The authors suggested that wider scanning area of SS-OCT should contain much more information than the area of SD-OCT. Other studies have reported that the wide-field scan of SS-OCT collects the information needed to diagnose glaucoma with excellent sensitivity and specificity 14 , 22 , 23 . Therefore, a wide-field scan of SS-OCT images should better reflect the structural damage that corresponds to functional loss than the more narrow scan of SD-OCT.…”
Section: Discussionmentioning
confidence: 99%
“…18,20,21,[26][27][28] However, their OCT device was a prototype and not commercially available, and their software also was under development; moreover, they did not evaluate pro- gression with serial OCT maps. After wide-field SS-OCT scanning and an SS-OCT probability map became commercially available, the diagnostic performance of wide-field SS-OCT RNFL maps for early glaucoma 29 and of the study by Hood 20 for prediction of future VF changes in preperimetric glaucoma patients, 30 respectively, were evaluated. However, structural progression was not evaluated in either study.…”
Section: Discussionmentioning
confidence: 99%